A meta-analysis and systematic review of different cyclin-dependent kinase 4/6 inhibitors in breast cancer - Zhang, Jialin; Xu, Xinyu; Zhou, Yeyue; Su, Jingyang; Wang, Jue (Frontiers in Oncology, 2025)
ObjectiveThe objective of this study was to assess the effectiveness and safety of CDK4/6 inhibitors in the treatment of hormone receptor-positive (HR+) breast cancer by using meta-analysis.MethodsTo gather comprehensive and reliable data for our analysis, we systematically searched multiple databases for relevant studies. We utilized RevMan5.3 software to perform the meta-analysis.ResultsFollowing a rigorous screening and evaluation process, we ultimately included a total of 13 studies in our analysis. Our findings showed that compared to endocrine therapy alone, the combination of CDK4/6 inhibitors with endocrine therapy significantly increased both PFS [HR 0.54 (95%CI: 0.50, 0.58), P<0.00001], OS [HR 0.77 (95%CI: 0.50, 0.58), P<0.00001] and ORR [RR 1.39 (95% CI: 1.21, 1.60), P<0.00001). However, it was also found that CDK4/6 inhibitors caused adverse drug reactions related to the blood system and digestive system (P<0.0001).ConclusionsOur meta-analysis demonstrates that the addition of CDK4/6 inhibitors to endocrine therapy can result in improved PFS and OS for HR+ breast cancer patients. Meanwhile, we recommend close monitoring and management of these potential side effects when utilizing these inhibitors in breast cancer treatment.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42023490499.